Cough Syncope, a Rare Presenting Symptom of Chiari I Malformation and Atlanto-Occipital Assimilation - Inês Carrilho Oliveira; Joana Carvalho; Luisa Oliveira (European Journal of Case Reports in Internal Medicine, 2020)
Chiari I malformation and atlanto-occipital assimilation are both fairly uncommon conditions. Symptoms usually present during adolescence or adulthood, typically consisting of headache or neck pain. Cough-associated syncope is an unusual presenting symptom. The diagnosis of this condition in a pulmonology department is even rarer. We report the case of a 62-year-old male referred to our pulmonology department due to complaints of cough-associated syncope. After several examinations, a pharyngeal CT scan incidentally showed low positioning of the cerebellar tonsils. Cerebral MRI confirmed the diagnosis of Chiari I malformation and atlanto-occipital assimilation and the patient was effectively treated with surgical decompression.